2016
DOI: 10.1002/jpln.201500384
|View full text |Cite
|
Sign up to set email alerts
|

Allocation and dynamics of C and N within plant–soil system of ash and beech

Abstract: Forest management requires a profound understanding of how tree species affect C and N cycles in ecosystems. The large C and N stocks in forest soils complicate research on the effects of tree species on C and N pools. In-situ 13 C and 15 N labeling in undisturbed, natural forests enable not only tracing of C and N fluxes, but also reveal insight into the interactions at the plant-soilatmosphere interface. In-situ dual 13 C and 15 N pulse labeling of 20 beeches (Fagus sylvatica L.) and 20 ashes (Fraxinus excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 61 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Mycorrhizal fungal hyphae are an important C pool in soil. Mycorrhizal fungi and fine roots transfer large proportions of primary production into soils, but the estimates vary substantially across studies (Janssens et al, ; Pausch & Kuzyakov, ; Sommer, Dippold, Flessa, & Kuzyakov, ). Additionally, the biological N fixation and nutrient mobilization from deep soils have increased soil fertility, prompting C sequestration (Araujo, Iwata, Jr, & Xavier, ; Balakrishna, Lakshmipathy, Bagyaraj, & Ashwin, ; Vallejo, Roldan, & Dick, ).…”
Section: Resultsmentioning
confidence: 99%
“…Mycorrhizal fungal hyphae are an important C pool in soil. Mycorrhizal fungi and fine roots transfer large proportions of primary production into soils, but the estimates vary substantially across studies (Janssens et al, ; Pausch & Kuzyakov, ; Sommer, Dippold, Flessa, & Kuzyakov, ). Additionally, the biological N fixation and nutrient mobilization from deep soils have increased soil fertility, prompting C sequestration (Araujo, Iwata, Jr, & Xavier, ; Balakrishna, Lakshmipathy, Bagyaraj, & Ashwin, ; Vallejo, Roldan, & Dick, ).…”
Section: Resultsmentioning
confidence: 99%
“…While reviews have suggested that, on average, half of soil respiration is autotrophic from recent photosynthate [77], the reported relative proportion of fixed C that is allocated belowground ranges from 10% to 90% [34]. Differences in C allocation between deciduous and evergreen trees, and trees with ectomycorrhizal (like most conifers) and arbuscular mycorrhizal (aspen have also arbuscular mycorrhizae) associations have been reported in literature [67,78,79]. Therefore, we hypothesize that the differences between SOC pools under aspen and conifer overstories are due to differences in belowground C allocation and microbial composition and activity in the rhizosphere.…”
Section: Belowground C Inputmentioning
confidence: 99%
“…Previous isotopic tracer studies have shown a strong coupling between recently fixed plant photosynthates and belowground C allocation to roots, soil microbes and respiratory fluxes (Bahn et al, 2013;Barthel et al, 2014;Epron et al, 2011;Hogberg et al, 2008;Jin and Evans, 2010;Sommer et al, 2016;Street et al, 2013;Subke et al, 2012;Tavi et al, 2013;Weng et al, 2017). The fate of this C is ultimately controlled by the composition and activity of soil biota, however our understanding of the below ground C flux and its partitioning amongst roots, mycorrhizae and free living soil microbes is still limited (De Deyn et al, 2008;Stuart Chapin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%